2008
DOI: 10.1007/s00383-008-2274-x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide does not affect the methylation status of prognostic important oncogenes Rassf1A and DCR2 in neuroblastoma cells

Abstract: Exposure of neuroblastoma cells to 100% CO(2) does not alter methylation of two prognostic relevant index genes. It seems therefore unlikely that effects on methylation levels within CO(2) pneumoperitoneum lead to epigenetic changes in neuroblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Hypoxia in particular, a known inductor of dediff erentiation which is correlated to a poor outcome in neuroblastoma, might contribute to this eff ect [7] . In previous studies we were unable to explain these observations in terms of cell proliferation [22] and, recently, DNA methylation [19] under in vitro conditions. In this study we investigated a third level, possibly explaining the higher metastatic rates of neuroblastoma cells after conditions mimicking pneumoperitoneum: the expression of promalignant genes.…”
Section: Discussionmentioning
confidence: 72%
“…Hypoxia in particular, a known inductor of dediff erentiation which is correlated to a poor outcome in neuroblastoma, might contribute to this eff ect [7] . In previous studies we were unable to explain these observations in terms of cell proliferation [22] and, recently, DNA methylation [19] under in vitro conditions. In this study we investigated a third level, possibly explaining the higher metastatic rates of neuroblastoma cells after conditions mimicking pneumoperitoneum: the expression of promalignant genes.…”
Section: Discussionmentioning
confidence: 72%
“…The few attempts to investigate CO 2 effects on NB cells have been focused on cell proliferation/migration, epigenetic changes, apoptosis, and expression of High Mobility Group Box (HMGB)-1 and c-MYC. 3,4,16,17 In previous studies, we evaluated alterations in cell redox status induced by CO 2 and its potential impact on human SH-SY5Y NB cells. Our results showed that in vitro simulated CO 2 pneumoperitoneum environment induces oxidative stress, leading to DNA damage followed by a significant attenuation of cell proliferation mediated by p53 activation.…”
Section: Discussionmentioning
confidence: 99%